Early Introduction of Power Mobility Devices for Children with Fukuyama Congenital Muscular Dystrophy and Its Psychological Impact on Caregivers: A Case Report - Hitomi Fujita (Pediatric Reports, 2023)
Recently, motorized mobility devices (or power mobility devices (PMDs)) have been introduced for infants and toddlers who lack the means for self-mobility. Previous reports have primarily focused on PMDs for individuals with cerebral palsy. Few have explored PMDs for individuals with neuromuscular diseases who have intellectual disabilities. This report presents a case study of the early introduction of a PMD for an infant with Fukuyama congenital muscular dystrophy and presents the results of an interview with the father regarding psychological aspects and the child’s manipulative abilities. The PMD was introduced at the age of 1 year and 10 months, and the changes during the 19 months after the introduction were evaluated six times, using the Assessment of Learning Powered mobility use tool (ALP). A semi-structured interview with the father was conducted 19 months after the introduction. The ALP evaluation and the interview were conducted by one physical therapist and two physical therapy students, and the results were shared with the hospital’s physical therapist and nurses at the nursing facility. This report provides a basis for expanding the scope of PMD use and for considering the family’s involvement, especially for the child.